Pengaruh Senam Hamil Terhadap Penurunan Nyeri Punggung Bawah Pada Ibu Hamil TM III di Praktek Mandiri Bidan Novia Br Karo Kec. Sunggal Kab. Deli Serdang Tahun 2023 - Yenni Fransiska B; Nur Azizah; Rosmani Sinaga (Jurnal Siti Rufaidah, 2024)
Background: Lower back pain is common in pregnant women, especially in the third trimester, due to physiological changes such as weight gain, shifts in the body’s center of gravity, and ligament relaxation. Prenatal exercise is a non-pharmacological method that improves flexibility, strengthens muscles, and enhances posture, reducing lower back pain. However, its implementation remains limited due to a lack of education and supporting facilities. Objective: This study evaluates the effect of prenatal exercise on lower back pain reduction in third-trimester pregnant women at the Independent Practice of Midwife Novia Br Karo, Sunggal District, Deli Serdang Regency. Method: A pre-experimental design with a one-group pretest-posttest approach was used. The study included 32 third-trimester pregnant women experiencing lower back pain. Prenatal exercise was provided, and pain levels were measured before and after using an observation sheet. Results: Before the intervention, most respondents (53.1%) reported moderate pain. After prenatal exercise, the majority (59.4%) experienced reduced pain in the mild category. The Wilcoxon test yielded a Z value of -3.122 with p = 0.002 (p < 0.05), indicating a significant effect of prenatal exercise in reducing lower back pain. Conclusion: Prenatal exercise effectively reduces lower back pain intensity in third-trimester pregnant women. It should be promoted as a non-pharmacological intervention for pregnancy-related back pain and incorporated into maternal health programs.